Effect of tidal regime on estuarine residence time spatial variation - Duarte, António A. L. Sampaio (2009)
The hydrology and the ecology of shallow estuaries are strongly influenced by the freshwater inflow and the adjacent open sea, due to tide and wind generated water exchange, creating salinity gradients, thermal stratification and assuring large transport of silt, organic material and inorganic nutrients into the estuarine waters. Nutrient enrichment is a key-factor for habitat degradation, leading to sensible structural changes in estuarine ecosystems with the consequent occurrence of episodic algal blooms. In the last two decades, the south arm of the Portuguese river Mondego estuary was stressed by an eutrophication process due to massive nutrient loading from urbanised areas and from intensively agricultural land runoff. The aim of this work is to calculate estuarine water residence time values, which are broadly recognised as important descriptors of estuarine circulation patterns and constitute key-parameters to assess estuarine eutrophication vulnerability. In fact, estuaries with nutrients residence time values, shorter than the algal cells doubling time, will inhibit algae blooms occurrence. The increase of estuarine flushing capacity can be seen as a management measure to mitigate or to invert eutrophication processes. In this work, the MONDEST model, a 2-DH water quality model, was developed and applied to calculate water residence time, at different simulated management scenarios. The results shows the effect of simulated tides on the spatial distribution of estuarine residence time values, which are related with the eutrophication gradients, observed in the Mondego estuary south arm during the last decades. This integrated model constitutes a powerful tool to support authorities’ decisions concerning the best water management practices and restoration measures for the environmental sustainable management of this complex ecosystem.